Internet browsing the web - Milner, Annalisa (Essential computers, 2000)
A step-by-step guide to browsing the World Wide Web using "Internet Explorer," explaining how to open a Web page, use the toolbar, navigate between pages, print Web pages, use a directory, master searching skills, and create a favorites list.